Peripheral vestibular pathology in Mondini dysplasia. (14th April 2016) - Kaya, Serdar; Hızlı, Ömer; Kaya, Fatıma Kübra; Monsanto, Rafael DaCosta; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract : Objectives/Hypothesis: In this study, our objective was to histopathologically analyze the peripheral vestibular system in patients with Mondini dysplasia. Study Design: Comparative human temporal bone study. Methods: We assessed the sensory epithelium of the human vestibular system with a focus on the number of type I and type II hair cells, as well as the total number of hair cells. We compared those numbers in our Mondini dysplasia group versus our control group. Results: The loss of type I and type II hair cells in the cristae of the superior, lateral, and posterior semicircular canals, as well as in the saccular and utricular macula, was significantly higher in our Mondini dysplasia group than in our control group. The total number of hair cells significantly decreased in the cristae of the superior, lateral, and posterior semicircular canals, as well as in the saccular and utricular macula, in our Mondini dysplasia group. Conclusion: Loss of vestibular hair cells can lead to vestibular dysfunction in patients with Mondini dysplasia. Level of Evidence: NA Laryngoscope, 127:206–209, 2017